Enhancing Reading Comprehension for Magister Degree Students Through Self-Reflection (Universitas Negeri Semarang, 2022)
Self-reflection has been hailed as a potential avenue into work-based learning. However, the purpose of this research is to use self-reflection to improve the reading skills of B2 and C1 students at the CEFR level. This finding is expected to be a reference for the education sector, government, business, and academia in promoting, designing, and implementing self-reflection learning in English reading. Two sets of analyses were performed in this study. To begin, the authors examine the self-reflection of master students enrolled in an English proficiency program. Second, the authors examine the Internet search for selfreflection learning in reading. More specifically, the authors used Google Classroom and web resources to analyse real-world data from a reading self-reflection task of 14 students in reading B2 and C1. Based on the findings from the examination of the identified selfreflection reading task, students still had some difficulties in understanding the context of the reading. Self-reflection has been identified as a key topic in talent development from the point of view of work-based learning. Policymakers, educators, researchers, and participants should investigate ways to encourage, create, and implement microlearning to help individuals learn on the right track through valid knowledge and ethical thinking.